Evaluation of Laboratory Waste Management at Mataram University as a Basis for Preparing Environmental Pollution Prevention Policies - Akhdiyat, Hendra R.; Sarjan, M.; Sjah, Taslim (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
This research discusses the application of the balance principle in laboratory waste management as a strategy to minimize environmental impacts. This principle aims to balance laboratory activities and environmental protection by reducing waste at the source, sorting it out, and using environmentally friendly waste processing technology. The research used a descriptive qualitative approach in the Mataram University laboratory. The research results show that applying the balance principle is still not optimal due to limited understanding, infrastructure and adequate policy support. Recommended strategies include implementing the 3R principle (Reduce, Reuse, Recycle), selecting safer chemicals, and increasing training and preparing clear SOPs. Waste identification reached (50%), with limitations in storage (44%) and transportation (43%). Management and final disposal were minimal (33% and 38%), increasing environmental risks. Documentation, reporting (43%), and regulatory compliance (43%) still need to be improved. The K3 aspect is quite good (54%), but emergency response procedures are still weak. Sustainable management (37%) and environmental monitoring (43%) lack effort in mitigating environmental impacts. Applying the principle of balance is important to achieve sustainable laboratory waste management.